Ethical blind spots in leadership: addressing unconscious bias in post-COVID workforce management - Stephanie Bilderback (Journal of Ethics in Entrepreneurship and Technology)
Purpose – The purpose of this study is to explore the concept of ethical blind spots in leadership and their implications for post-COVID workforce management. As hybrid work models, generational shifts and heightened accountability reshape workplace dynamics, many leaders unintentionally perpetuate biases that harm organizational culture. The study examines how leaders can proactively address unconscious biases and ethical blind spots to foster inclusive, transparent and adaptive workplaces. In addition, it evaluates the role of public feedback in ethical decision-making, distinguishing between constructive accountability and performative compliance. Design/methodology/approach – This study adopts a theoretical approach, integrating ethical leadership theories, unconscious bias frameworks and generational management models. It draws on moral psychology and behavioral ethics to explore how leaders develop blind spots and offers practical strategies to address them. The analysis leverages recent literature on post-pandemic workforce challenges, including hybrid work structures, cancel culture, generational accountability mechanisms and the risks of performative diversity, equity and inclusion (DEI) efforts. A specific focus is placed on distinguishing between appropriate and inappropriate public feedback, as well as on the implications of leaders appearing to embrace feedback without real change. Findings – Ethical blind spots in leadership often stem from unconscious biases, proximity bias in hybrid work environments, performative allyship and digital perfectionism. These blind spots can hinder DEI efforts, erode trust and diminish employee engagement. The study finds that leaders who fail to address these biases risk fostering a toxic workplace culture. Practical tools, such as bias audits, psychological safety protocols and authentic engagement with younger employees, can help leaders mitigate these risks and create more ethical organizational practices. Originality/value – This study contributes to the growing discourse on ethical leadership by addressing the underexplored issue of ethical blind spots in post-COVID workforce management. The study highlights the risks of unmanaged biases in hybrid work environments, generational tensions and performative digital behaviors. It offers a comprehensive framework for leaders to recognize and address their biases, fostering inclusive, adaptive workplaces that meet the expectations of a more socially conscious workforce.